(untitled) (Desenvolvimento em Questão, 2026)
The text discusses the use of strategic planning as an instrument to boost family farming in the Santa Edwiges Agroecological Community, located in Chapada dos Guimarães, Mato Grosso. The main goal is to develop an integrated strategic plan for the community, emphasizing the relevance of agroecology in the transition to sustainability. To this end, techniques such as SWOT analysis, the Balanced Scorecard (BSC) and the 5W2H action plan were used, based on qualitative studies and interviews conducted with farmers in the region. The findings highlight challenges such as low education levels, inadequate infrastructure, problems with access to materials and transportation, as well as the demand for more government support and strategic alliances. The discussions indicate that the combination of traditional knowledge and management practices can enhance the socio-economic and environmental sustainability of the community, fostering food security and local progress. The conclusion is that strategic planning is crucial to overcoming the challenges of family farming and promoting the transition to agroecology in communities with similar characteristics.